2009
DOI: 10.1002/bem.20517
|View full text |Cite
|
Sign up to set email alerts
|

Changes in synaptic efficacy and seizure susceptibility in rat brain slices following extremely low‐frequency electromagnetic field exposure

Abstract: The effects of electromagnetic fields (EMFs) on living organisms are recently a focus of scientific interest, as they may influence everyday life in several ways. Although the neural effects of EMFs have been subject to a considerable number of investigations, the results are difficult to compare since dissimilar exposure protocols have been applied on different preparations or animals. In the present series of experiments, whole rats or excised rat brain slices were exposed to a reference level-intensity (250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 49 publications
2
24
0
Order By: Relevance
“…Basic synaptic functions were characterized by the amplitude and slope of evoked field potentials. An earlier study (Varró et al, 2009) has shown that whole‐body chronic (4 × 15 h on four consecutive days) exposure of adult rats increased the amplitude of field responses in neocortical and hippocampal slices, although not significantly. In the present study, significant increases in amplitude were observed, we demonstrated that the hippocampal slices were sensitive to both types of treatment (fetal 0.5 mT, newborn 3 mT), whereas neocortical slices seemed to be responsive mostly to the newborn treatment.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Basic synaptic functions were characterized by the amplitude and slope of evoked field potentials. An earlier study (Varró et al, 2009) has shown that whole‐body chronic (4 × 15 h on four consecutive days) exposure of adult rats increased the amplitude of field responses in neocortical and hippocampal slices, although not significantly. In the present study, significant increases in amplitude were observed, we demonstrated that the hippocampal slices were sensitive to both types of treatment (fetal 0.5 mT, newborn 3 mT), whereas neocortical slices seemed to be responsive mostly to the newborn treatment.…”
Section: Discussionmentioning
confidence: 91%
“…It seems that EMF exposure exerts significant effects on synaptic activity (e.g. Varró et al, 2009), but the changes strongly depend on the specific parameters of EMF.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the efficiency of electric field induction depends on the relative sizes of coil and target (Weissman et al, 1992; Deng et al, 2013), thus the electric fields induced by human coils in small in vitro targets are different to those generated in the human brain, so that information obtained cannot be directly translated back to the clinic. In low-intensity stimulation (LI-rMS) studies, solenoids (Di Loreto et al, 2009; Varro et al, 2009) or coils made “in house” have been applied to one-off experiments on cultured neurons/slices (Ahmed and Wieraszko, 2009; Rotem et al, 2014) or isolated nerves (Maccabee et al, 1993; Basham et al, 2009; RamRakhyani et al, 2013; Ahmed and Wieraszko, 2015) that do not permit on-going stimulation sessions to model treatment-based protocols. Moreover, given that NIBS acts on complex neural circuits, stimulation parameters should ideally be assessed in culture models which retain some neural circuitry: e.g., organotypic hippocampal (Hausmann et al, 2001; Hogan and Wieraszko, 2004; Vlachos et al, 2012; Lenz et al, 2016) and cortico-striatal slices, hindbrain explants (Chedotal et al, 1997; Letellier et al, 2009) or microfluidic circuit cultures (Szelechowski et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in neuronal electrophysiology, evoked potentials and EEG traces have been reported 12. Varrò et al 12 described a decrease in basic synaptic activity as a reduction in amplitude of evoked potentials in rat brain slice preparation when exposed to an electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Varrò et al 12 described a decrease in basic synaptic activity as a reduction in amplitude of evoked potentials in rat brain slice preparation when exposed to an electromagnetic field.…”
Section: Introductionmentioning
confidence: 99%